EFFECTIVENESS OF LEARNERS’ INTEGRATION OF TECHNOLOGY IN LERANING: A PHENOMENOLOGICAL STUDY INVESTIGATING LEARNER AUTONOMY AND PERSONALIZED LEARNING - Noor , Laila (UICELL, 2023)
This phenomenological study explores the lived experiences of adult English as a Foreign Language (EFL) learners integrating PowerPoint presentations into their classroom oral presentations. Data was collected from undergraduate students from Bangladesh and USA from semi-structured interviews. Following Braun and Clarke's (2006) thematic analysis, data were analyzed. The findings showed that the use of PowerPoint presentations was found to foster learners' autonomy and personalized learning. In addition, adult EFL learners employed various strategies to navigate the challenges. The study offers a detailed perspective on how PowerPoint supports the presentation of oral content, the obstacles learners encounter, and their strategic solutions to optimize learning, thereby promoting autonomy and personalized education. This research will contribute to a more comprehensive understanding of EFL learning and offers practical implications for utilizing PowerPoint effectively in EFL classrooms. Further research is recommended to extend this exploration into diverse EFL contexts and demographic groups. Keywords: Learners technology, PowerPoint, oral presentation, EFL learners